Liquidity, inflation and asset prices in a time-varying framework for the euro area - Christiane Baumeister; Eveline Durinck; Gert Peersman (National Bank of Belgium, 2008)
In this paper, we investigate how the dynamic effects of excess liquidity shocks on economic activity, asset prices and inflation differ over time. We show that the impact varies considerably over time, depends on the source of increased liquidity (M1, M3-M1 or credit) and the underlying state of the economy (asset price boom-bust, business cycle, inflation cycle, credit cycle and monetary policy stance).
Keywords: E31; E32; E44; E51; E52; 330; Liquidity; asset prices; inflation; time-varying coefficients; Liquidität; Inflationserwartung; Konjunktur; Geldpolitik; Eurozone; EU-Staaten